Triton X-100 catalyzed synthesis of α-aminophosphonates - Nemallapudi Bakthavatchala Reddy; Chereddy Syama Sundar; Chinthaparthi Radha Rani; Kunda Uma Maheswara Rao; Sandip Kumar Nayak; Cirandur Suresh Reddy (Arabian Journal of Chemistry, 2016)
Synthesis of α-aminophosphonates by a three-component condensation of an aldehyde, amines and dialkyl phosphites in the presence of a non-ionic surfactant Triton X-100 catalyst at 70 °C in aqueous medium is accomplished. The advantages are high yield, mild reaction conditions, simple work-up and eco-friendliness. All the newly-synthesized compounds (4a–j) exhibited moderate in vitro antibacterial and antifungal activities.